Association of Concussion History and Prolonged Recovery in Youth. Issue 6 (4th November 2022) - Chizuk, Haley M.; Cunningham, Adam; Horn, Emily C.; Thapar, Raj S.; Willer, Barry S.; Leddy, John J.; Haider, Mohammad N.
Abstract : Objective: To determine the number of prior concussions associated with increased incidence of persistent postconcussive symptoms (PPCS) in a cohort of acutely concussed pediatric patients. Design: Prospective observational cohort study. Setting: Three university-affiliated concussion clinics. Participants: Two hundred seventy participants (14.9 ± 1.9 years, 62% male, 54% with prior concussion) were assessed within 14 days of concussion and followed to clinical recovery. Participants with a second head injury before clinical recovery were excluded. Measures: and Main Outcome: Concussion history, current injury characteristics, recovery time, and risk for prolonged recovery from current concussion. Results: There was no statistically significant change in PPCS risk for participants with 0, 1 or 2 prior concussions; however, participants with 3 or more prior concussions had a significantly greater risk of PPCS. Twelve participants sustained a subsequent concussion after clinical recovery from their first injury and were treated as a separate cohort. Our secondary analysis found that these participants took longer to recover and had a greater incidence of PPCS during recovery from their latest concussion. Conclusion: Pediatric patients with a history of 3 or more concussions are at greater risk of PPCS than those with fewer than 3 prior concussions.